Effects of low-protein diets supplemented with indispensable amino acids on growth performance, intestinal morphology and immunological parameters in 13 to 35 kg pigs. (23rd May 2016) - Peng, X.; Hu, L.; Liu, Y.; Yan, C.; Fang, Z. F.; Lin, Y.; Xu, S. Y.; Li, J.; Wu, C. M.; Chen, D. W.; Sun, H.; Wu, D.; et al.
Abstract : The objective of this study was to determine if a moderate or high reduction of dietary CP, supplemented with indispensable amino acids (IAA), would affect growth, intestinal morphology and immunological parameters of pigs. A total of 40 barrows (initial BW=13.50±0.50 kg, 45±2 day of age) were used in a completely randomized block design, and allocated to four dietary treatments containing CP levels at 20.00%, 17.16%, 15.30% and 13.90%, respectively. Industrial AA were added to meet the IAA requirements of pigs. After 4-week feeding, blood and tissue samples were obtained from pigs. The results showed that reducing dietary CP level decreased average daily gain, plasma urea nitrogen concentration and relative organ weights of liver and pancreas ( P <0.01), and increased feed conversion ratio ( P <0.01). P igs fed the 13.90% CP diet had significantly lower growth performance than that of pigs fed higher CP at 20.00%, 17.16% or 15.30%. Moreover, reducing dietary CP level decreased villous height in duodenum ( P <0.01) and crypt depth in duodenum, jejunum and ileum ( P <0.01). The reduction in the dietary CP level increased plasma concentrations of methionine, alanine ( P <0.01) and lysine ( P <0.05), and decreased arginine ( P <0.05). Intriguingly, reducing dietary CP level from 20.00% to 13.90% resulted in a significant decrease in plasma concentration of IgG ( P <0.05), percentage of CD3 + T cells of the peripheral blood ( P <0.01), also down-regulated the mRNA abundance of innate immunity-related genes on toll-like receptor 4, myeloid differentiation factor 88 ( P <0.01) and nuclear factor kappa B ( P <0.05) in the ileum. These results indicate that reducing dietary CP level from 20.00% to 15.30%, supplemented with IAA, had no significant effect on growth performance and had a limited effect on immunological parameters. However, a further reduction of dietary CP level up to 13.90% would lead to poor growth performance and organ development, associated with the modifications of intestinal morphology and immune function.